A patient-specific induced pluripotent stem cell model for West syndrome caused by ST3GAL3 deficiency. (December 2018) - Diepen, Laura; Buettner, Falk; Hoffmann, Dirk; Thiesler, Christina; von Bohlen und Halbach, Oliver; von Bohlen und Halbach, Viola; Jensen, Lars; Steinemann, Doris; Edvardson, Simon; Elpeleg, Orly; Schambach, Axel; Gerardy-Schahn, Rita; et al.
Abstract ST3GAL3 encodes the Golgi enzyme beta-galactoside-alpha-2, 3-sialyltransferase-III that in humans forms, among others, the sialyl Lewis a (sLea ) epitope on proteins. Functionally deleterious variants in this gene were previously identified in patients with either non-syndromic or syndromic intellectual disability such as West syndrome, an age-dependent epileptic encephalopathic syndrome associated with developmental arrest or regression. The aim of this study was to further elucidate the molecular and cellular mechanisms causing West syndrome by lack of ST3GAL3 function. For this purpose we generated induced pluripotent stem cell (iPSC) lines from fibroblasts obtained from a patient with West syndrome, carrying a variant in exon 12 (c.958G>C, p.(Ala320Pro)) ofST3GAL3, and a healthy sibling, using lentiviral reprogramming. iPSCs and cortical neurons derived thereof were analysed by lectin blots, mRNA sequencing, adherence assays, and FACS. While no significant difference was observed at stem cell or fibroblast level between patient and control cells, patient-derived cortical neurons displayed an altered lectin blot staining pattern, enhanced adherence to a poly-l -ornithine/laminin-coated surface and decreased levels of neurons expressing T-box transcription factor brain 1. Our results suggest that changes in the sialylation pattern on the surface of specific neuronal cell types affect adhesive interactions during development, which in turn may cause subtle changes in tissue composition that could result in the occurrence of epilepsy and might impair neural development to an extent that is detrimental to the development and maintenance of normal cognitive functions.